Mapping Critical and Creative Thinking Skills: Evidence from Elementary School Students - Wiwin, Wiwin Winarti; Mubarok, Mubarok Somantri; Asep, Asep Kurnia Jayadinata; Hany, Hany Handayani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to map the profile of critical and creative thinking skills and analyze the relationship between the two. Method: The method used was quantitative descriptive correlational involving 112 students as a sample. Data was collected through test instruments that included various indicators of critical and creative thinking, then analyzed using the Spearman's rho correlation test. Results: The results showed that the critical thinking profile of students was in the medium category, with the highest achievement in the interpretation aspect but weak in strategy formulation. Meanwhile, the creative thinking profile showed high scores in the fluency aspect, but low in the flexibility and originality aspects. The results of the correlation test showed a significant positive relationship between critical and creative thinking skills. Novelty: This indicates that strengthening critical reasoning is an important foundation in producing innovative creative solutions. This research recommends the need for a learning model that challenges students' strategic abilities and originality.